Preliminary investigation of the use of Raman spectroscopy to predict beef spoilage in different types of packaging. (July 2020) - Yang, Hongbo; Hopkins, David L.; Zhang, Yimin; Zhu, Lixian; Dong, Pengcheng; Wang, Xinyi; Mao, Yanwei; Luo, Xin; Fowler, Stephanie M.
Abstract: In this study, pH, meat color analysis, microbial counts and Raman spectroscopic data were obtained from beef steaks stored at 4 °C for up to 21 days using two different packaging methods: vacuum (VP) and modified atmosphere packaging (MAP). Models using partial least square regression (PLSR), indicated that Raman spectroscopy was able to predict total viable counts (TVC) and lactic acid bacteria (LAB) measured at 21d post mortem (TVC in VP: R 2 cv = 0.99, RMSEP = 0.61; TVC in MAP: R 2 cv = 0.90, RMSEP = 0.38; LAB in VP: R 2 cv = 0.99, RMSEP = 0.54; LAB in MAP: R 2 cv = 0.75, RMSEP = 0.60). The results of this study demonstrate that Raman spectroscopy may have potential for the rapid determination of meat spoilage. Highlights: Raman spectroscopy has potential for the rapid determination of meat spoilage. Preliminary investigation suggests total viable counts at 21 d can be predicted. Models indicated the potential to predict lactic acid bacteria.